Identidad e Identificación: Investigación de Campo como Herramienta de Aprendizaje en el Diseño de Marcas - Nájera Galeas, Carlos Enrique (2017)
Brands as scenarios that represent the set of attributes and values of a product, company or city, are the result of an exhaustive study of real contexts. Field research as a method allows the observer to intervene in a physical environment, starting from the site visit, then observing the place and photographing it, schematizing the images and finally outlining concepts. This process involves ethnography as a tool that allows the designer to speculate less about reality. Its result consolidates a set of actions that strengthen the positive image of the product, whose deduction is the "BRAND", improves its perception at local and international level obtaining a competitive advantage over others. The design and creation of a Brand is a way of reinforcing the realization of a new value system expressed in the recognition of goods or services characteristic of the product, where the designer plays a fundamental role in the representation of actions during the investigation. Finally, it is important to strengthen the teaching of the design of brands based on methods and techniques that allow a graphic representation resulting from a previous research that consolidates the methodological processes of the designer.